Analysis of risk factors linked to social educator profession in different residential settings of Alicante Province - Jorge Heliz Llopis; Ignasi Navarro Sória; Noelia Tortosa Casado; Pablo Jodra Jiménez (Revista Sobre la Infancia y la Adolescencia)
One of the most important professions in the field of intervention with underage at social risk that are cared for in different residential settings is, undoubtedly, that of the social educator. In that sense, although there are many professionals involved with these underage (psychologists, social workers, psychiatrists, teachers, etc.), social educators are the ones who, through the carrying out of functions specific to their profession, often work as the "front line" of action, given that they are the ones who are more in touch with the underage and therefore the most likely to be exposed to different variables that could eventually put them in a situation of risk of psycho-social problems related to their work. Hence, the task of identifying the risk variables related to the teaching profession becomes a key objective in order to prevent the occurrence of likely problems that could undermine their psychosocial health. Therefore, through this communication we intend to expose the results that we obtained with a sample of 50 educators who perform their work in different residential-type services in the province of Alicante.